2023
DOI: 10.1002/ctm2.1267
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation inhibition sensitises renal medullary carcinoma tumours to platinum chemotherapy

Abstract: Background Renal medullary carcinoma (RMC) is a highly aggressive cancer in need of new therapeutic strategies. The neddylation pathway can protect cells from DNA damage induced by the platinum‐based chemotherapy used in RMC. We investigated if neddylation inhibition with pevonedistat will synergistically enhance antitumour effects of platinum‐based chemotherapy in RMC. Methods We evaluated the IC50 concentrations of the neddylation‐activating enzyme inhibitor pevonedistat in vitro in RMC cell lines. Bliss syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Previous research has shown that NEDD8-activating enzyme (NAE) inhibitor, mln4924, enhances tumor sensitivity to oncolytic viro [ 39 ], platinum [ 40 ], and cisplatin [ 41 ] treatment through different mechanisms. Due to the lack of effective treatment for TNBC, PTX treatment resistance significantly affects patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that NEDD8-activating enzyme (NAE) inhibitor, mln4924, enhances tumor sensitivity to oncolytic viro [ 39 ], platinum [ 40 ], and cisplatin [ 41 ] treatment through different mechanisms. Due to the lack of effective treatment for TNBC, PTX treatment resistance significantly affects patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MLN4924 induces G2 cell cycle arrest and DNA damage in esophageal squamous cell carcinoma cells and sensitizes them to cisplatin [ 31 ]. Moreover, MLN4924 synergizes with carboplatin to inhibit renal medullary carcinoma cells by inhibiting DNA damage repair [ 32 ]. Likewise, treatment with MLN4924 was found to sensitize HNSCC cells to ionizing radiation (IR) and enhanced IR-induced xenografts inhibition in nude mice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, p53 ∆31/∆31 cells exhibited a typical feature of cells from FA patients: the decreased capacity to repair DNA interstrand crosslinks induced by mitomycin C. Importantly, out of the 12 FA genes downregulated by p53 in mouse cells, 9 were also downregulated by p53 in human fibroblasts, and an increased expression of FA genes could be used as a marker of human tumor progression [26]. Furthermore, HCT116 cells (human colon carcinoma cells expressing a WT p53) were sensitized to mitomycin C upon p53 activation [26], and p53 activation improved platinum-based anti-cancer chemotherapy in a preclinical model [34]. Thus, again, our observations in mice appeared relevant to human disease processes.…”
Section: The Plot Thickens: Germline P53 Activation Underlies Feature...mentioning
confidence: 99%